ANALISIS PENGARUH PERTUMBUHAN EKONOMI, TINGKAT PENDIDIKAN, ANGKATAN KERJA, DAN PERPAJAKAN TERHADAP DISPARITAS PENDAPATAN DI PROVINSI JAWA TIMUR - Ditta Rosalitta; Sri Muljaningsih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The benchmark for success in the administration of inter-regional governance is to create harmony between economic growth and social welfare that is just and equitable. The goal of this study was to see how much economic growth, education level, labor force, and taxation influenced income disparities in East Java Province. This type of research is classified as quantitative descriptive research. The IBM SPSS (Statistical Package for Social Science) Version 26 was used as the analytical tool in this study. The data for this study were gathered from the Central Statistics Agency of East Java Province between 2010 and 2020 and the Ministry of Finance of the Republic of Indonesia between 2010 and 2020. According to the findings of this study, economic growth (X1) and education level (X2) have no significant effect on income disparities in East Java Province. While the labor force (X3) has a significant impact on income disparities in East Java Province, taxation (X4) has a significant impact.